INTERRELATION AND INTERDEPENDENCE OF CLINICAL SYNDROMES FROM DEGREE OF STENOSIS OF VERTEBRAL CANAL ON LUMBAR LEVEL - Z. V. Koshkariova; V. A. Sorokovikov; A. V. Gorbunov; V. G. Brukhanov; L. V. Rodionova; O. V. Skliarenko (Acta Biomedica Scientifica)
There were 81 patients with vertebral canal stenosis under observation. All patients underwent complex examination: study of clinical neurological status; review spondylography of lumbar part of the spine; MRI of lumbar part of the spine; multispiral CT with myelography of lumbar part of the spine; functional spondylography of lumbar part of the spine with load; the study of morphometry of vertebral canal, dural sack and vertebra body by designed method; the study of acute phase proteins in blood. Conducted complex research revealed that improved classification of stenosis of vertebral canal reflects direct dependence of severity of clinical-neurological manifestations from the degree of stenosis. It also has been marked that reduced concentration of α2-macroglobulin in blood manifests itself in negative regulation of cells of immune system. And an increase of classic rheumatoid factor (Ig M-RF), α1-antitripsin and α1-acid glycoprotein in blood serum leads to reduction of inflammatory and immune response. Revealed direct co-dependence of severity of disease and degree of stenosis gives a possibility to develop more precise program of conservative and surgical treatment.